2015
DOI: 10.1002/cdq.12019
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Help Career Services: A Case Report

Abstract: Self-help career services represent an important form of career intervention rarely described in the literature. Using a case-report approach, the author describes this type of career intervention, which was guided by cognitive information processing theory and Holland's (1997) typological theory. The report offers an example of appropriately identifying client readiness to engage in career counseling using a 3-tier model for service delivery composed of direct, brief, and self-help interventions. It also demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…Responding to an increased student demand for career services, the Career Center at Florida State University in Tallahassee implemented a differentiated service delivery model (i.e., self‐help services, brief staff‐assisted services, and individual case‐managed services) based on cognitive information processing (CIP) theory (Sampson, Reardon, Peterson, & Lenz, ) more than 40 years ago. Self‐help services, which differ from “counselor‐free” (Kronholz, , p. 282) services, are designed for more independent use, in that counselors are relied on in a time‐limited format to refer users to appropriate educational and occupational information. Individual case‐managed services provide the same type of services as brief staff‐assisted services, but on an extended basis because of the client's low readiness, as evidenced by his or her low decision‐making capability, high complexity of issues compounding the decision‐making process, and possible mental health issues.…”
mentioning
confidence: 99%
“…Responding to an increased student demand for career services, the Career Center at Florida State University in Tallahassee implemented a differentiated service delivery model (i.e., self‐help services, brief staff‐assisted services, and individual case‐managed services) based on cognitive information processing (CIP) theory (Sampson, Reardon, Peterson, & Lenz, ) more than 40 years ago. Self‐help services, which differ from “counselor‐free” (Kronholz, , p. 282) services, are designed for more independent use, in that counselors are relied on in a time‐limited format to refer users to appropriate educational and occupational information. Individual case‐managed services provide the same type of services as brief staff‐assisted services, but on an extended basis because of the client's low readiness, as evidenced by his or her low decision‐making capability, high complexity of issues compounding the decision‐making process, and possible mental health issues.…”
mentioning
confidence: 99%
“…She indicated that her career planning needs were fulfilled for now and that she would return to the career center if needed. Readers wanting more information about this case can read the article by Kronholz (2015).…”
Section: Appendix a Three Csi Case Studiesmentioning
confidence: 99%
“…For the most part, the Guide’s developmental process appears congruent with the recommendations of the four-step process derived from the extant literature. The next phase in developing the refined Guide would involve converting it into an online resource to leverage on the use of technology in self-reliant career exploration and planning (Gati & Asulin-Peretz, 2011; Kronholz, 2015).…”
Section: Developing and Refining The Journey To The West Guidementioning
confidence: 99%